Analisis Kesesuaian Lahan Untuk Tanaman Cengkeh Di Kabupaten Agam - Fikri Haykal; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This research aim to know : 1) The land characteristic in Agam Regency; 2) The actual Suitability for clove plant in Agam Regency; 3) The function of Agam Regency region; 4) The wide of potential land for planting cengkeh in Agam Regency. This research uses maching methode in analizing the land suitability and overal binary for analizing the function of area. Based on the result of research the researcher knows that : 1) The indicators which is very influential for the land characteristic in Agam Regency are fall of rain, air temperature, land drainage, the texture of the land and slope; 2) The wide of land are very suitable 8842,47 ha, suitable 65883,62 ha, marginal suitable 50719,7 ha and no suitable 82871,47 ha; 3) Protected region is about 9450,78 ha, support region is about 29581,02 ha, cultivation region for annual plants is about 103815,2 ha and cultivation region for seasonal plants is about 65648,38 ha; 4) The potential of land Which is very suitable for the function of the annual plants cultivation region is about 853,7 ha and suitable is about 27858,03 ha.